The importance of the Kafirkala monument in the development of Central Sughd (Genius Repository, 2023)
In this article, the Kafirkala monument, which made an important contribution to the development of the Central Sugdian statehood on the Great Silk Road , and the receptions and ceremonies of this monument , which were not just an ordinary residence of the rulers of Samarkand at the end of the 7th century, but had a special national significance here. and revealed to have been an important residence where ceremonies were held.